WINGKAS POLITICAL MENTALITIES BEFORE THE ’INALIENABLE AGRARIAN COMMUNITY’ AND THE MAPUCHE PEOPLE. (FROM IBÁÑEZ TO IBÁÑEZ, 1927- 1958) - Samaniego Mesías, Augusto (Revista de Historia Social y de las Mentalidades, 2025)
A core and distinctive aspect of the 20 th century policies toward the Mapuche people promoted by the majority society, including political parties and the Chilean State has been to protect the inalienable nature of indigenous agricultural communities . We therefore make a distinction between two main trends. The first trend involves the actions and logic of those who promoted turning ove r indigenous lands to the market, thereby tailoring indigenous identities and rights to meet the needs of homogenous citizenship, state and laws; namely, the liberal id eological and political matrix of “assimilation”. The second trend includes those who support the indivisibility of the common land held by the indigenous community , claiming it to be the historical foundation of their ethnic-social identity and comm on indigenous rights.